Взаємозалежності об’єму кузова і вантажопідйомності та маси машин для внесення твердих органічних добрив - Лімонт, А. С.; Лімонт, З. А.; Limont, A.; Limont, Z. (ЦНТУ, 2022)
Мета роботи полягала в дослідженні зв’язку між об’ємом кузова машин для внесення ТОД і їх вантажопідйомністю та масою, а також зворотної зміни вантажопідйомності і маси цих машин залежно від об’єму кузова. В першому випадку результативною ознакою був об’єм кузова, а факторіальними – вантажопідйомність і маса машин, а в другому – за результативні ознаки прийняті вантажопідйомність і маса машин, а в якості факторіальної ознаки визначений об’єм кузова машин для внесення ТОД. Обробка зібраних даних здійснена на засадах математичної статистики і зокрема кореляційно- регресійного аналізу та з використанням стандартних комп’ютерних програм. Коефіцієнт кореляції між об’ємом кузова машин для внесення ТОД і вантажопідйомністю машин, між вантажопідйомністю машин і об’ємом кузова мав однакове значення 0,920. Однакове значення мали і кореляційні відношення об’єму кузова на вантажопідйомність та вантажопідйомності машин на об’єм кузова, яке становило 0,935. Кількісну зміну об’єму кузова залежно від маси машин і маси машин залежно від об’єму кузова краще описують рівняння прямолінійної регресії з додатними кутовими коефіцієнтами (R2=0,824). При збільшенні маси машин на 1 т за її зміни від 1 до 13,7 т об’єм кузова зростає на 1,8 м3. Із збільшенням об’єму кузова на 1 м3 за його зміни від 1,9 до 25,7 м3 маса кузовних машин зростає на 0,456 т. The aim of the study was to investigate the relationship between the body volume of solid organic fertilizer (TOD) machines and their load capacity and weight, as well as the inverse change in load capacity and weight of these machines depending on the body volume. In the first case, the effective feature was the volume of the body, and the factorial – load capacity and weight of machines, and in the second – the effective characteristics were taken to be the load capacity and weight of machines, and as a factorial feature was the body size of the machine. The study included 47 brands and models of body machines for TOD, including 14 machines manufactured by enterprises located in the former Soviet Union, and 9 and 24 produced by “KUHN” and “Strautmann”, respectively. The value of the studied resultant and factorial features was found using information from domestic and foreign literature. The collected data are processed on the basis of mathematical statistics and in particular correlationregression analysis and using standard computer programs. The correlation coefficient between the volume of the body of the machine for applying TOD and the load capacity of the machines, between the load capacity of the machines and the volume of the body was the same value 0,920. The correlation ratios of body volume to load capacity and machine load capacity to body volume, which was 0.935, were equally important. Between the volume of the body and the weight of the cars as well as between the weight of the cars and the volume of the body, the observed values of the correlation coefficients also had the same value, equal to 0.908 and positive. In the two paired relationships studied, the correlations between body volume to machine weight and machine mass to body volume had the same value of 0.861. Quantitative changes in body volume depending on the weight of the machines and the weight of the machines depending on the volume of the body are better described by the equations of rectilinear regression with positive angular coefficients (R2 = 0.824). As the weight of the machines increases by 1 ton and changes from 1 to 13.7 tons, the body volume increases by 1.8 m3. With an increase in body volume by 1 m3 with its change from 1.9 to 25.7 m3, the weight of body cars increases by 0.456 tons. Quantitative change in body volume depending on load capacity and load capacity depending on body volume should be described by equations of rectilinear regressions with positive angular coefficients (R2 = 0.847). According to the calculated R2 coefficients equal to 0.875, the approximation of the experimental values of the effective features of body volume and load capacity to their aligned values was provided by approximating the change in body volume and load capacity by the equations of slowly increasing power functions. According to the angular coefficients of the equations of lines when increasing the load capacity of body machines by 1 ton for its change from 2 to 34 tons, the body volume increases by 0.799 m3, and when increasing the body volume by 1 m3 for its changes from 1.9 to 25, 7 m3 capacity of machines increases by 0.581 tons.
Interdependence of Body Volume and Load Capacity and Weight of Machines for Application of Solid Organic Fertilizers
Keywords: кузовні машини для внесення твердих органічних добрив; об’єм кузова; вантажопідйомність; маса; рівняння регресії; body machines for solid organic fertilizers; body volume; load capacity; mass; regression equations